Politik Ekonomi UU Perbankan Syariah Peluang dan Tantangan Regulasi Industri Perbankan Syariah - WIBISONO, YUSUF (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
Building an effective legal and regulatory framework for Islamic banking is imperative. Initiative to enact Islamic banking laws in Indonesia can be regarded in this respect. The objective of this paper is to examine the critical issues in Islamic banking laws. This paper examines and highlights the main features of Islamic banking laws. It is suggested that the main goal of the laws are to enhance Shari’ compliance and promoting stability of the system. Despite the progress achieved through this approach, it is recommended that Islamic banking development needs more efforts and initiatives. This paper also attempts to provide an analysis of future direction in the development of Islamic banking industry in Indonesia.